2016
DOI: 10.1002/star.201600158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipid types on complexation and some physicochemical properties of bambara groundnut starch

Abstract: This study investigated the effect of stearic acid, linoleic acid, and lysophosphatidylcholine on complex formation and physicochemical properties of bambara starch in comparison with potato starch. The complexation index reached maximum at 2% lipid concentration. Bambara starch complexed better with stearic acid than with linoleic acid and lysophosphatidylcholine. A similar trend was observed for potato starch but to a lesser extent. All lipids significantly reduced the peak and setback viscosities of bambara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 55 publications
3
56
0
Order By: Relevance
“…Native BGS pasted with palmitic acid showed further reduction in peak and breakdown viscosities, while annealed BGS pasted with palmitic acid further showed a greater reduction in these parameters (Table ). Previous studies similarly found significant reductions in peak viscosity after pasting of BGS with stearic acid, linoleic acid and lysophosphatidylcholine (Oyeyinka et al ., ). The reductions in peak viscosity have been attributed to the formation of amylose–lipid complexes (Oyeyinka et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Native BGS pasted with palmitic acid showed further reduction in peak and breakdown viscosities, while annealed BGS pasted with palmitic acid further showed a greater reduction in these parameters (Table ). Previous studies similarly found significant reductions in peak viscosity after pasting of BGS with stearic acid, linoleic acid and lysophosphatidylcholine (Oyeyinka et al ., ). The reductions in peak viscosity have been attributed to the formation of amylose–lipid complexes (Oyeyinka et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Previous research modified Bambara groundnut starch (BGS) using annealing (Adebowale & Lawal, ), oxidation, acetylation (Adebowale et al ., ), carboxymethylation (Afolabi, ) or lipids (Oyeyinka et al ., ,c,d). Adebowale & Lawal () found that ANN caused significant reduction in swelling power and peak viscosity of BGS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reported studies on improving physicochemical properties of starch films with lipids have focused mainly on conventional starch sources like cereals and tubers. However, starches from pulses such as cowpea ( Vigna unguiculata ) and bambara ( Vigna subterrenea ) with high amylose content (22% to 78%; Hoover and others ; Oyeyinka and others ; Oyeyinka and others ), may be a promising matrix for making films. Bambara groundnut is a pulse of African origin.…”
Section: Introductionmentioning
confidence: 99%
“…In Southern Africa, this crop is neglected and grown mainly for subsistence. Recently, bambara starch was modified with lipids for improved functionality (Oyeyinka and others ,c). The use of bambara starch in complexation with lipids and in biofilm application is unique in many ways.…”
Section: Introductionmentioning
confidence: 99%